2015
DOI: 10.1080/01446193.2015.1029504
|View full text |Cite
|
Sign up to set email alerts
|

Safety by design: dialogues between designers and builders using virtual reality

Abstract: © 2015 The Author(s). Published by Taylor & Francis.Designers can contribute to enhancing the safety of construction work by considering how their decisions impact on both the physical environment in which construction workers operate and the means and methods they use. To do so, however, designers require knowledge about safety hazards on site and the opportunity to examine their designs early in projects. Through a set of studies virtual reality tools were used to examine the potential for collaborative dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 21 publications
2
54
1
1
Order By: Relevance
“…The groupings used for comparison were based on literature that suggests that issues such as experience, training, educational and professional background can affect DfS awareness, knowledge and skills of construction practitioners. The groupings are as follows: (Smallwood, 2004;Sacks et al, 2015;Hayne et al, 2017). The size of respondent's firm was also considered in view of research evidence regarding the relationship between firm size and implementation of H&S practices (Kheni et al 2008;Manu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The groupings used for comparison were based on literature that suggests that issues such as experience, training, educational and professional background can affect DfS awareness, knowledge and skills of construction practitioners. The groupings are as follows: (Smallwood, 2004;Sacks et al, 2015;Hayne et al, 2017). The size of respondent's firm was also considered in view of research evidence regarding the relationship between firm size and implementation of H&S practices (Kheni et al 2008;Manu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bhoir and Esmaeili (2015) used the VR technologies in the construction safety management program, and they significantly reduced the rate of accident in a result. Sacks et al (2015) showed that VR technologies are highly beneficial for designers to appreciate the implications of designs on the safety program. These applications of VR could run numerous drills or unique scenarios that will provide the user with a reallife feeling of a potential threat.…”
Section: Construction Safety Managementmentioning
confidence: 99%
“…Several studies have been conducted on project stakeholders' influence on health and safety risk management. Some of the authors have focused on safety responsibility among designers during the design phase [8][9][10][11] while others focused on the role of clients on health and safety management [12][13][14][15][16]. They maintain that clients have a major role in project implementation, and therefore, they should push for the safety requirements.…”
Section: Introductionmentioning
confidence: 99%